Inhibition of 2-Oxoglutarate Dehydrogenase as a Chemical Model of Acute Hypobaric Hypoxia - Graf, Anastasia; Ksenofontov, Alexander; Bunik, Victoria (Frontiers in Medicine, 2021)
Both hypoxia and inhibition of 2-oxoglutarate dehydrogenase complex (OGDHC) are known to change cellular amino acid pools, but the quantitative comparison of the metabolic and physiological outcomes has not been done. We hypothesize that OGDHC inhibition models metabolic changes caused by hypoxia, as both perturb the respiratory chain function, limiting either the NADH (OGDHC inhibition) or oxygen (hypoxia) supply. In the current study, we quantify the changes in the amino acid metabolism after OGDHC inhibition in the highly sensitive to hypoxia cerebellum and compare them to the earlier characterized changes after acute hypobaric hypoxia. In addition, the associated physiological effects are characterized and compared. A specific OGDHC inhibitor succinyl phosphonate (SP) is shown to act similar to hypoxia, increasing levels of many amino acids in the cerebellum of non-pregnant rats, without affecting those in the pregnant rats. Compared with hypoxia, stronger effects of SP in non-pregnant rats are observed on the levels of cerebellar amino acids, electrocardiography (ECG), and freezing time. In pregnant rats, hypoxia affects ECG and behavior more than SP, although none of the stressors significantly change the levels of cerebellar amino acids. The biochemical differences underlying the different physiological actions of SP and hypoxia are revealed by correlation analysis of the studied parameters. The negative correlations of cerebellar amino acids with OGDHC and/or tryptophan, shown to arise after the action of SP and hypoxia, discriminate the overall metabolic action of the stressors. More negative correlations are induced in the non-pregnant rats by hypoxia, and in the pregnant rats by SP. Thus, our findings indicate that the OGDHC inhibition mimics the action of acute hypobaric hypoxia on the cerebellar amino acid levels, but a better prediction of the physiological outcomes requires assessment of integral network changes, such as increases in the negative correlations among the amino acids, OGDHC, and/or tryptophan.